Four new feather mite species of the genus Anhemialges Gaud, 1958 (Astigmata: Analgidae) from China - Chang, Hui-Qun; Wang, Zi-Ying; Liu, Huai (Zootaxa, 2018)
Four new species of the feather mite genus Anhemialges (Astigmata: Analgidae) are described from passeriform birds in China: A. lioparus sp. nov. from the Golden–breasted Fulvetta Lioparus chrysotis (Passeriformes, Paradoxornithidae); A. aegithalos sp. nov. from the Black–throated Tit Aegithalos concinnus (Passeriformes, Aegithalidae); A. seicercus sp. nov. from the Golden–spectacled Warbler Seicercus burkii (Passeriformes, Phylloscopidae); and A. zosterops sp. nov. from the Oriental White–eye Zosterops palpebrosus (Passeriformes, Zosteropidae).